Literature Review Efektifitas Latihan Fisik Tunggal Dan Kombinasi Terhadap Penurunan Kadar Glukosa Darah Pasien Diabetes Mellitus Tipe 2 - Bahriah, Bahriah; Syahrul, Syahrul; Tahir, Takdir (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Diabetes Mellitus is a disease that can cause sufferers to lose physical function. The cases will continue to increase from year to year. If not treated immediately, diabetes can cause dangerous chronic conditions. Preventing complications through treatment such as medication and controlling blood glucose levels was needed. The study aimed to evaluate the effectiveness of single and combined physical exercises in reducing blood glucose levels in Type 2 DM patients. The literature review design used three international databases PubMed, ClinicalKey for Nursing, and the Cochrane Library. The literature review was performed on articles published between 2011 to 2022 using Randomized Control Trial designs. A total of nine articles met the inclusion criteria. Results showed that the single physical exercise intervention group and the combined physical exercise proved effective in reducing blood glucose levels compared to the control group. In addition, physical exercises also affect HbA1c, body mass, insulin levels, insulin resistance, adiponectin, IL-6, and short physical performance battery (SPPB). It can conclude through evidence-based studies that single or combined physical exercise interventions are proven to reduce blood glucose levels and HbA1c, also lowering the weight in type 2 DM sufferers. It is suggested to perform a specific review on physical exercises which are better in reducing the blood glucose level as well as other indicators.